Zonotope-based Interval Estimation for Discrete-Time Linear Switched Systems⁎This work was partially supported by National Natural Science Foundation of China (61773145, 61973098, 61703296) and the Fund from the National Defense Key Discipline of Space Exploration, Landing and Reentry in Harbin Institute of Technology under Grant HIT.KLOF.2018.073. Issue 2 (2020) - Zhang, Wenhan; Wang, Zhenhua; Raïssi, Tarek; Dinh, Thach Ngoc; Dimirovski, Georgi M.
Abstract: This paper is concerned with the interval estimation for discrete-time linear switched systems affected by unknown disturbances and noises. A novel interval estimation approach is proposed by integrating robust observer design with zonotopic techniques. By introducing L ∞ technique into observer design, the proposed approach is effective in attenuating the influence of unknown disturbances and noises, and improving the accuracy of interval estimation. Based on the designed observer, the interval estimation can be obtained by using zonotopic analysis. Numerical simulation results are conducted to demonstrate the feasibility and effectiveness of the proposed approach.